Student Entrepreneurial Intention Model in Medan City - M Rikwan E.S; Dewi Comala Sari; Edy Sahputra Sitepu (Politeknik Negeri Bengkalis, 2021)
This study aims to analyze how the influence of the variables of intellectual intelligence, emotional intelligence, and spiritual intelligence on students' entrepreneurial intentions, using the intervening variables of student creativity and learning achievement. The research was conducted at polytechnic higher education institutions (public and private) in Medan City. The number of research samples was 400 people, and the data were analyzed using a structural equation model with Amos software. For the direct effect of exogenous variables, it was found that students' intellectual intelligence and creativity had a statistically significant impact. In contrast, the variables of emotional intelligence, spiritual intelligence, and learning achievement were not statistically significant. The indirect impact variables used to estimate entrepreneurial intentions are statistically significant, except for the emotional intelligence variable. Furthermore, as an intervening variable, the learning achievement variable provides a partial mediation effect in mediating the influence of the intellectual intelligence variable on entrepreneurial intentions. The learning achievement variable also provides a partial mediation effect in mediating the impact of the spiritual intelligence variable on entrepreneurial intentions. In contrast, the learning achievement variable provides no mediation effect in mediating the influence of the emotional intelligence variable on entrepreneurial intentions.